2017
DOI: 10.1097/mpg.0000000000001337
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid–based Formula in Cow's Milk Allergy

Abstract: Long-term treatment with AAF is safe and allows adequate body growth in children with CMA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 25 publications
(41 reference statements)
2
36
0
1
Order By: Relevance
“…Glutamic acid, in particular, has been suggested to downregulate appetite during feeding by interacting with specific receptors in the oral cavity and gastrointestinal tract. However recent studies have shown no negative effect of feeding AA formulas in infants; on the contrary, they may be beneficial for growth [ 65 ].…”
Section: The Role Of Diet In the Management Of Food Allergymentioning
confidence: 99%
“…Glutamic acid, in particular, has been suggested to downregulate appetite during feeding by interacting with specific receptors in the oral cavity and gastrointestinal tract. However recent studies have shown no negative effect of feeding AA formulas in infants; on the contrary, they may be beneficial for growth [ 65 ].…”
Section: The Role Of Diet In the Management Of Food Allergymentioning
confidence: 99%
“…Paediatrician recommendations stress careful nutritional guidance to manage CMA[3,6,28,29] , including the use of an adapted formula that meets the nutritional needs of non-breastfed infants and young children[30,31]. Therefore, evidence on the safety and suitability of these formulas should be obtained from children with CMA in particular, as recently reported for some eHFs[23,24] or AAFs[32,33]. Growth parameters of the children fed the TeHCF were within normal range throughout the 3-mo period, indicating that this hypoallergenic formula is safe.…”
Section: Discussionmentioning
confidence: 99%
“…Однако при этом, даже если удается компенсировать дефицит белковой составляющей рациона, потребление витами-нов и минеральных веществ остается недостаточным. [31][32][33] Миф 11. «Нужно вылечить дисбактериоз, и аллергия пройдет» Сегодня уже не вызывает сомнений, что микробиота кишечника является фактором, в значительной степени влияющим на здоровье человека.…”
Section: козье молоко не является гипоаллергенным при ме-нение продуunclassified